A Tandem Ring‐Opening/Michael Addition/Ring‐Closure Sequence for the Regiospecific Synthesis of 5‐Hydroxy‐4, 5‐dihydroisoxazoles. Issue 8 (11th July 2019) - Wang, Xuesong; Chen, Yu; Chen, Xin; Zhang, Xueying; Guan, Weiwei; Li, Youbin
Abstract: An effective and highly regiospecific strategy for the synthesis of 5‐hydroxy‐4, 5‐dihydroisoxazoles is described via a tandem reaction including ring‐opening, Michael addition, and ring‐closure in one pot under mild conditions. Diverse structural 5‐hydroxy‐4, 5‐dihydroisoxazoles were afforded in up to 96% yield for 21 examples. This strategy is highly efficient, environmentally friendly, and metal free. Abstract : Blackjack ! An effective and highly regiospecific method for the synthesis of 5‐hydroxy‐4, 5‐dihydroisoxazoles from the condensation of 4‐iodo‐5‐hydroxy‐furan‐2‐ones with hydroxylamine hydrochloride is described under mild conditions. 21 examples of diverse structural 5‐hydroxy‐4, 5‐dihydroisoxazoles were afforded in up to 96% yield. The ring‐opening, Michael addition, and ring‐closure reactions were involved in this tandem procedure. This strategy is highly efficient, environmentally friendly and metal free.